Ankle and Foot Deformities in Children - Inarejos Clemente, Emilio J.; Aparisi Gómez, Maria Pilar; Catala March, Jordi; Restrepo, Ricardo (Seminars in Musculoskeletal Radiology, 2023)
Ankle and foot deformity is one of the most common musculoskeletal disorders in children and a leading cause of functional impairment and diminished quality of life when not treated. A spectrum of conditions may produce foot and ankle deformities, with congenital disorders the most frequent cause, followed by acquired conditions. Congenital disorders include congenital talipes equinovarus or congenital clubfoot, metatarsus adductus, skewfoot, congenital vertical talus, and tarsal coalition.Some of these deformities are frequent and easily diagnosed based on clinical features, but clinical overlap between pathologies can be challenging. Thus imaging plays a paramount role in evaluating these patients. Radiographs are the first imaging modality of choice, but they may not be sufficient in infants due to the lack of ossification of the tarsal bones. Ultrasonography allows not only a detailed visualization of the cartilaginous structures but also permits a dynamic study of the foot and ankle. Computed tomography may be necessary in certain conditions such as tarsal coalitions.
Keywords: pediatric foot; congenital; clubfoot; metatarsus adductus; tarsal coalition